2012
DOI: 10.1186/1471-2180-12-277
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of pili-specific bacteriophages: genome sequence of IncM plasmid-dependent RNA phage M

Abstract: BackgroundBacteriophages of the Leviviridae family are small RNA viruses with linear, positive-sense, single-stranded RNA genomes that encode only four proteins. All phages of this family require bacterial pili to attach to and infect cells. Leviviridae phages utilizing F-pili for this purpose have been extensively studied. RNA phages specific for conjugative plasmid-encoded pili other than that of plasmid F have been isolated, but are much less understood and their relation to the F-pili-specific phages in ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 48 publications
0
21
0
Order By: Relevance
“…9 top). Like Enterobacteria phage M, it may also encode a +1 frameshift lysis protein inside of the RdRp gene (53). The predicted lysis protein contains a gram-negative signal peptide and a transmembrane domain and may form pores in the plasma membrane, dissipating proton motive force and inducing cell autolysis (54).…”
Section: Rna Phage Potential Hosts and Ecologymentioning
confidence: 99%
“…9 top). Like Enterobacteria phage M, it may also encode a +1 frameshift lysis protein inside of the RdRp gene (53). The predicted lysis protein contains a gram-negative signal peptide and a transmembrane domain and may form pores in the plasma membrane, dissipating proton motive force and inducing cell autolysis (54).…”
Section: Rna Phage Potential Hosts and Ecologymentioning
confidence: 99%
“…Previously, the A 2 protein of levivirus Qβ and the E protein of the microvirus φ X174 were shown to be ‘protein antibiotics’ that inhibit the MurA and MraY steps of the PG synthesis pathway 24 . Here, we investigated the mechanism of action of an unrelated lysis protein, Lys M , of the Escherichia coli levivirus M 5 . We show that Lys M inhibits the translocation of the final lipid-linked PG precursor called lipid II across the cytoplasmic membrane by interfering with the activity of MurJ.…”
mentioning
confidence: 99%
“…1a) and found that lysis genes appear to have evolved at different sites after speciation of the phage to infect cells with new pili receptors 5 . In particular, levivirus M has its lys M gene embedded in the +1 reading frame of rep .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Out of such efforts, 19 new genomes of icosahedral RNA phages [286], genomes from the phages M [287], C-1 and HgalI [288], DL52 and DL54 [289], from a so-called JS-like group [290] and of the phages EC and MB [291], have been described.…”
Section: Future Perspectivesmentioning
confidence: 99%